Intervenção pedagógica e construção de noções étnicas por meio da pesquisa escolar: um estudo piagetiano - Almeida, Elizângela Áreas Ferreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Based on Piaget's theory of the construction of social knowledge, this study reflects on how pedagogical interventions with constructivist principles can contribute to the construction of ethnic and racial notions of the students, putting into practice what is established by Law 10.639/2003 regarding the teaching of African and African-Brazilian history, culture and literature at schools. The paper presents two guiding focus: on the one hand the ethnic and racial issues and on the other hand a very common practice at schools - school research. Thus, it aimed to investigate the construction of ethnic and racial notions in adolescent students and intervene in this process through active methodologies inspired by the constructivism. Therefore, an educational intervention was carried out, revisiting the practice of school research and giving it a new didactic and pedagogical treatment, so to constitute a viable tool in the teaching-learning, anchored in the discovery and investigative spirit, giving learners greater autonomy in this ongoing process of knowledge construction. The study gathered 28 teenagers, aged from 12 to 14 years old, elementary school students from public schools in São Paulo. The chosen methodological design was action research, according to the following phases: 1st - initial diagnosis by clinical interviews, in order to probe the beliefs of students on ethnic notions; 2nd - pedagogical intervention, consisting of 23 activities involving school research and enrichment activities for it; 3rd - Final assessment of the investigated action, by reapplying the same instrument used in the initial diagnosis. Collected data were categorized quantitatively and qualitatively and analysis of the results showed an evolution in the way the investigated subjects understood the ethnic and racial issues, as 75% of these individuals have advanced in their ethnic constructions, going from elementary and naive thoughts, typical for level I...

Fundamentado na teoria piagetiana sobre a construção do conhecimento social, este estudo traz algumas reflexões sobre como intervenções pedagógicas com princípios construtivistas podem contribuir para a construção de noções étnico-raciais de escolares, pondo em prática o que é estabelecido pela lei 10.639/2003 com relação ao ensino da história, cultura e literatura africanas e afro-brasileiras nas escolas. O trabalho apresenta dois focos norteadores: de um lado as questões étnico-raciais e de outro uma prática tão comum nas escolas - a pesquisa escolar. Sendo assim, teve como objetivo investigar a construção de noções étnico-raciais em estudantes adolescentes e intervir nesse processo por meio de metodologias ativas, inspiradas no construtivismo. Para tanto, foi realizada uma intervenção pedagógica, revisitando a prática da pesquisa escolar e atribuindo-lhe um novo tratamento didático-pedagógico, de modo que se configure como um instrumento viável no processo ensino-aprendizagem, ancorado na descoberta e no espírito investigativo, conferindo aos educandos maior autonomia neste processo contínuo de construção de conhecimentos. Participaram desta pesquisa 28 adolescentes, com idades entre 12 e 14 anos, alunos do ensino fundamental da rede pública estadual do interior paulista. O delineamento metodológico escolhido foi o da pesquisa-ação, de acordo com as seguintes fases: 1ª - diagnóstico inicial, mediante entrevistas clínicas, com o objetivo de sondar as crenças dos alunos sobre noções étnicas; 2ª - intervenção pedagógica, composta por 23 atividades envolvendo a pesquisa escolar e atividades complementares a ela; 3ª - avaliação final da investiga-ação, por meio da reaplicação do mesmo instrumento utilizado no diagnóstico inicial. Os dados obtidos foram categorizados quanti e qualitativamente e a análise dos resultados evidenciou uma evolução na forma como os sujeitos investigados...
Keywords: Piaget, Jean, 1896-1980; Aprendizagem; Conhecimento e aprendizagem; Inclusão em educação; Educação; Programas de ação afirmativa na educação; Mainstreaming in education